If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -9 = -63 Reorder the terms: -9 + 3a = -63 Solving -9 + 3a = -63 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3a = -63 + 9 Combine like terms: -9 + 9 = 0 0 + 3a = -63 + 9 3a = -63 + 9 Combine like terms: -63 + 9 = -54 3a = -54 Divide each side by '3'. a = -18 Simplifying a = -18
| -5x+12=2(x+1) | | .20(10)+x=.50(x+10) | | 2/16=8/ | | x+6=(2x-3) | | 9x-8-1x+4= | | 0.06x-0.18=.18 | | 2/16=8/? | | Y/11=7/17 | | b+a=58 | | 2x+-2=-5x | | 5=-16t^2+44 | | (2u+4y-3)(2u-7y)= | | 8(z-6)+7z-1= | | 12x-4e^5= | | 2-3x=2+4x | | ((2*t)/15)-(((3*t)-5)/20)=((t/5)-3) | | 14t-33=14t-8 | | 6(x-4)=-4 | | 56=71 | | 4e^5= | | 4e^5=x | | -2x+y=3y-6x | | 20x+5y=285 | | 3(y-1)=c | | 8x^2(4x^3+2x^2+3x+1)= | | -7(3x-4)=-49 | | 6(2x-1)=4x+18 | | (X-2)(x+6)=180 | | -3(1+5)+4=-104 | | 3-x/42 | | 5/7-3Y=-2 | | 6-5[4-(7y-2)]= |